Pelatihan Media Dan Bahan Ajar Inovatif Untuk Moderasi Tiga Dosa Pendidikan Melalui Perangkat Kecerdasan Buatan - Uji Windiatmoko, Doni; Dwi Yulian Prakoso, Riyan; Afif Nabila, Luthfannisa; Alfin Faujie, Indy; Putra Nugroho, Gandhi (LPPM Universitas Pekalongan, 2025)
ABSTRACT Based on the lack of knowledge and skills of partner teachers in using artificial intelligence (AI) tools to develop innovative media and teaching materials, this community service activity is an important thing to do as a concrete step to solve partner problems. The purpose of the training is to introduce and improve the skills of partner teachers in using AI platforms to develop innovative media and teaching materials based on Purbalingga's local wisdom to moderate the three educational sins. The training participants were 5 third grade teachers and 5 fourth grade teachers at MI Istiqomah Sambas Purbalingga. The implementation method was carried out by (1) socialization; (2) training; (3) mentoring; (4) evaluation; (5) program sustainability. The results of this training implementation are (1) an increase in partner teacher knowledge as seen from the difference in pretest and posttest scores of 20.3; (2) an increase in partner teacher skills in using AI tools to develop innovative teaching media and materials as evidenced by the work in the form of AI-based teaching materials that are in accordance with their respective subjects, while integrating elements of Purbalingga's local wisdom. In addition, the teaching materials produced also support the moderation of three educational sins-bullying, sexual violence, and intolerance-through educational and informative learning media. The conclusion of this study shows that AI training can help teachers in creating more adaptive and contextualized teaching materials, as well as having a positive impact on the learning environment. This program is expected to be a sustainable model for teacher capacity building in the future. Keywords: AI, teachers, teaching materials, media, local wisdom of Purbalingga, moderation of the three sins of education ABSTRAK Didasari pada minimnya pengetahuan dan keterampilan guru mitra dalam menggunakan perangkat artificial intelligence (AI) untuk menyusun media dan bahan ajar inovatif, kegiatan pengabdian masyarakat ini menjadi hal penting untuk dilakukan sebagai langkah konkret untuk memecahkan masalah mitra. Tujuan pelatihan tersebut ialah pengenalan dan peningkatan keterampilan guru mitra dalam menggunakan platform AI untuk menyusun media dan bahan ajar inovatif berbasis kearifan lokal Purbalingga untuk memoderasi tiga dosa pendidikan. Peserta pelatihan berjumlah 5 guru kelas III dan 5 guru kelas IV di MI Istiqomah Sambas Purbalingga. Metode pelaksanaan dilakukan dengan cara (1) sosialisasi; (2) pelatihan; (3) pendampingan; (4) evaluasi; (5) keberlanjutan program. Adapun hasil pelaksanaan pelatihan ini berupa terdapat (1) peningkatan pengetahuan guru mitra yang ditinjau dari perbedaan hasil skor pretest dan posttest sebesar 20,3; (2) peningkatan keterampilan guru mitra dalam penggunaan perangkat AI untuk menyusun media dan bahan ajar inovatif dibuktikan dengan hasil karya berupa bahan ajar berbasis AI yang sesuai dengan mata pelajaran masing-masing, sekaligus mengintegrasikan unsur kearifan lokal Purbalingga. Selain itu, bahan ajar yang dihasilkan juga mendukung moderasi tiga dosa pendidikan—perundungan, kekerasan seksual, dan intoleransi—melalui media pembelajaran yang mendidik dan informatif. Kesimpulan dari penelitian ini menunjukkan bahwa pelatihan AI dapat membantu guru dalam menciptakan bahan ajar yang lebih adaptif dan kontekstual, serta memberikan dampak positif pada lingkungan pembelajaran. Program ini diharapkan dapat menjadi model berkelanjutan bagi pengembangan kapasitas guru di masa depan. Kata kunci: AI, guru, bahan ajar, media, kearifan lokal purbalingga, moderasi tiga dosa pendidikan